Pengaruh Emulgator Terhadap Stabilitas Krim Antifungi Daun Ketepeng Cina - Widyah Ismawati S. , Herlina Rante, Maria Ulfa , Zulham (Jurnal Farmasi dan Ilmu Pengobatan, 2016)
One of traditional medicine which can be used to treat ringworm and skin disorder caused by skin parasites is ketepeng cina. Ethyl acetate extracts ketepeng cina are known to have antifungal activity against Candida albicans This research was aimed to determine effect of the concentration of emulsifier on the stability of the cream. The research using 3 variations the concentration of emulsifier that is 1%, 3% and 5%. Before formulating extracts tested antifungal activity against Candida albicans with concentration of 2.5%, 5% and 10%. Cream then tested the physical properties and antifungal activity against Candida albicans. The test results the activity extract with a concentration of 10% have a diameter that is the most excellent inhibitory 7.88 mm. Evaluation of cream shows that variation of emulsifier does not give effect to the change in the organoleptic (color and odor), emulsion type, adhesive power, dispersive power, viscosity and drops dispersed. But, affect the measurement of volume kriming in Formula 1, Formula 2 and Formula 4. cream activity test results showed that the cream with extract ketepeng cina that is formula 4, formula 5 and formula 6 has a diameter of inhibition respectively 9.01 mm, 9.81 mm and 10.11 mm.